Exopolysaccharide-producing bacteria enhanced Pb immobilization and influenced the microbiome composition in rhizosphere soil of pakchoi (Brassica chinensis L.) - Cao, Ruiwen; Zhang, Yiling; Ju, Yuhao; Wang, Wei; Zhao, Yanqiu; Liu, Nan; Zhang, Gangrui; Wang, Xingbao; Xie, Xuesong; Dai, Cunxi; Liu, Yue; Yin, Hongfei; et al. (Frontiers in Microbiology, 2023)
Lead (Pb) contamination of planting soils is increasingly serious, leading to harmful effects on soil microflora and food safety. Exopolysaccharides (EPSs) are carbohydrate polymers produced and secreted by microorganisms, which are efficient biosorbent materials and has been widely used in wastewater treatment to remove heavy metals. However, the effects and underlying mechanism of EPS-producing marine bacteria on soil metal immobilization, plant growth and health remain unclear. The potential of Pseudoalteromonas agarivorans Hao 2018, a high EPS-producing marine bacterium, to produce EPS in soil filtrate, immobilize Pb, and inhibit its uptake by pakchoi (Brassica chinensis L.) was studied in this work. The effects of strain Hao 2018 on the biomass, quality, and rhizospheric soil bacterial community of pakchoi in Pb-contaminated soil were further investigated. The results showed that Hao 2018 reduced the Pb concentration in soil filtrate (16%–75%), and its EPS production increased in the presence of Pb2+. When compared to the control, Hao 2018 remarkably enhanced pakchoi biomass (10.3%–14.3%), decreased Pb content in edible tissues (14.5%–39.2%) and roots (41.3%–41.9%), and reduced the available Pb content (34.8%–38.1%) in the Pb-contaminated soil. Inoculation with Hao 2018 raised the pH of the soil, the activity of several enzymes (alkaline phosphatase, urease, and dehydrogenase), the nitrogen content (NH4+-N and NO3−-N), and the pakchoi quality (Vc and soluble protein content), while also raising the relative abundance of bacteria that promote plant growth and immobilize metals, such as Streptomyces and Sphingomonas. In conclusion, Hao 2018 reduced the available Pb in soil and pakchoi Pb absorption by increasing the pH and activity of multiple enzymes and regulating microbiome composition in rhizospheric soil.